2012
DOI: 10.1007/s12029-012-9407-0
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Adenocarcinoma in Young Adults in a Moroccan Population

Abstract: This is the first reported study in our patient population of young patients with PAC. The data suggested that patients with younger age seem to have the same poor prognosis as the typical (older) patient population with PAC. No risk factors have been identified. However, this study is retrospective and more larger studies are needed in this young population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
6
6
0
Order By: Relevance
“…The main differences between the two PDAC groups were seen in demographic data. EOPC patients in our population were more frequently males, in agreement with previous studies [ 5 – 7 , 12 , 13 , 36 , 37 ]. In addition, our EOPC patients were less frequently of white British background and more commonly Asian or from ‘any other white background’.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The main differences between the two PDAC groups were seen in demographic data. EOPC patients in our population were more frequently males, in agreement with previous studies [ 5 – 7 , 12 , 13 , 36 , 37 ]. In addition, our EOPC patients were less frequently of white British background and more commonly Asian or from ‘any other white background’.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the highest incidence of EOPC patients was reported in two independent studies conducted in North Africa, in Morocco [ 36 ] and Egypt [ 41 ]: 17% of PDAC patients were younger than 45 years in Morocco [ 36 ], and almost 25% in the East Nile Delta were under the age of 50 [ 41 ]. In both countries the male to female ratio was around 2:1, in accordance with other reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35][36] The results showed that the proportion of PDAC patients with diabetes mellitus was 23.9%, which is comparable to that reported by several authors. 1,22,28 Similar to the findings of other studies, the presenting symptoms for PDAC were dominated in our series by weight loss (68.6%), abdominal pain (64.2%) and jaundice (53.7%). 27,36,37 Present study showed that the tumor was located to the pancreatic head in the majority of cases (71.6%), This was in accordance with the results reported in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…1 It is the 12 th most frequent cancer worldwide with 338 000 new cases and the 7 th most common cause of cancer death in the world with 331 000 deaths per year in both sexes in 2012. 2,3 Pancreatic ductal adenocarcinoma (PDAC) is the most common malignancy of the pancreas.…”
Section: Introductionmentioning
confidence: 99%